Sirtuin1 and Sirtuin3 gene polymorphisms and acute myocardial infarction susceptibility - Habieb, Mona Salah El-Din; Abdel-Aziz, Walaa Farid; Ismail, Abdel Hamid Abdo; Sallam, Khadija Metwali Ahmed; El-Shafie, Maathir Kamel (Meta Gene, 2021)
Acute myocardial infarction is one of the leading causes of death in the developed countries. This study aimed to study the association between sirtuin1 (SIRT1) gene polymorphism rs7069102 and promoter variant rs12293349 of sirtuin3 (SIRT3) gene and MI. 150 subjects were enrolled: 100 myocardial infarction (MI) patients and 50 healthy individuals. All subjects were investigated for blood glucose, lipid profile, cardiac markers (creatine kinase (CK-MB) and troponin I (TnI) by ELISA and genotyping of SIRT1 rs7069102 and SIRT3 rs12293349 by real time PCR. MI cases had significantly higher prevalence of SIRT1 rs7069102 GG genotype and G allele when compared to controls. GG genotype and G allele elevated the risk of MI. The dominant (CG + GG versus CC) and recessive (GG versus CC + CG) models both showed a significant difference in the distribution of rs7069102 genotypes. Under the dominant model, total cholesterol, LDLc and CK-MB levels were significantly higher in CG + GG patients. While under the recessive model, GG patients showed significantly increased FBG, 2 h PPG, HbA1c, total cholesterol, and LDLc (p = 0.001). By univariate and multivariate logistic regression analysis, LDLc and total cholesterol were the only independent determining variables. Considering the SIRT3 rs12293349, there is no significant differences between patients and controls. According to the findings, carrying the variant-type G allele of the SIRT1 rs7069102 was linked to an elevated risk of MI suggesting that this genetic variation could be a promising MI marker in an Egyptian population.